Gambaran Inspeksi Sanitasi Sumur Gali dengan Kandungan Bakteriologis Air Sumur Gali di Wilayah Kerja Puskesmas Sikumana Kota Kupang Tahun 2022 - Emanuel Dappa; Marilyn S, Junias; Mustakim Sahdan (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Dug wells are a source of clean water that is widely used in Indonesia. This is in accordance with data obtained from BPS for 2020, where 2020 as many as 33.44% of households in Indonesia still use wells as a source of clean water. Clean water sources from wells are water sources that are easily contaminated with E-coli or colcoliformcteria. This is because the sanitary conditions of the wells are not in accordance with health requirements. This study aims to describe the sanitary conditions of dug wells with bacteriological content in dug well water. This research is descriptive research with a quantitative approach. The research was conducted in the working area of ​​the Sikumana Health Center, Kupang City, from August to September 2022. The sample in this study was 34 dug wells. Data analysis in this research is univariate data analysis. The results showed that the sanitary conditions of dug wells in the Sikumana Health Center work area, Kupang City in 2022, namely 14.7% of dug wells had a low risk of contamination, 47% had a moderate risk of contamination, 32.3% had a high risk of contamination, and as many as 5.8% has a very high risk of contamination. The results of the research on the bacteriological content of dug well water showed that out of 34 samples of dug well water, 58.8% of dug well water contained E-coli bacteria. Health promotion efforts and guidance to the community are needed to overcome the problem of dug-well sanitation.